Conversations About Challenges in Computing - Bruaset, Are Magnus; Tveito, Aslak (Springer International Publishing : Imprint: Springer, 2013)
This text sheds light on how mathematical models and computing can help understanding and prediction of complicated physical processes; how communication networks should be designed and implemented to meet the increasingly challenging requirements from users; and how modern engineering principles can lead to better and more robust software systems.   Through interviews with 12 internationally recognized researchers within these fields, conducted by the well-known science writer Dana Mackenzie and the science journalist Kathrine Aspaas, the reader gets views on recent achievements and future challenges.  .